Evaluasi Kinerja Website Universitas XXX Menggunakan Metode WebQual dan Performance Testing - Gultom, Manorang (JITU, 2025)
University websites play an important role as a means of disseminating information, providing administrative services, and facilitating interaction between the academic community and the public. This study aims to evaluate the performance of the XXX University website through a combination of WebQual 4.0 to assess user perceptions and performance testing to measure technical performance. The research method used is quantitative with a descriptive and experimental design. Perception data was collected through a WebQual questionnaire involving 170 respondents selected using purposive sampling. Descriptive analysis was performed using the Respondent Achievement Rate (TCR) formula, while performance testing was carried out using GTmetrix to measure performance score and speed index parameters. The results showed that the quality of the website service based on user perception was in the very high category with an average RAC of 93.6%, especially in the dimensions of usability (94.1%) and service interaction (93.9%). However, the dimension of information quality received a relatively lower score (92.8%), particularly in the indicators of relevance and depth of information. On the other hand, the performance testing results showed suboptimal technical performance with an average performance score of only 15% and a speed index of over 11 seconds, far from the ideal standard of <3 seconds. The website performed better in the morning than at night, indicating server capacity limitations and the impact of traffic load. The results of this study conclude that the XXX University website is considered superior in terms of service quality based on user perception, but is still weak in terms of technical aspects. Therefore, comprehensive improvements and continuous monitoring are required. The combined approach of WebQual and performance testing has proven to be effective in providing a comprehensive overview of the strengths and weaknesses of the website as a basis for further development strategies.